The use of price-to-earnings-to-growth (PEG) ratios to predict share performance on the JSE - T. I'Ons; M. Ward (South African Journal of Business Management, 2012)
The effectiveness of the Price Earnings Growth ratio as a valuation tool has been a topical debate amongst analysts ever since being popularised by Lynch (1989). This study examines the appropriateness of the fair value criteria of a PEG of 1,0, as proposed by Lynch (PEGL), and compares this with the time-series based, share specific model, proposed by Trombley (2008) (PEGT). In addition, the study analyses several factors which influence the accuracy of analyst's forecasts (viz. the number of analysts' contributions, the dispersion of forecasts and the forecast horizon), with the objective of identifying an optimal trading rule based on the PEG ratio. We find consistent outperformance of the PEGT model. We also note (unexpectedly) that analyst's forecasting accuracy may have a less significant impact on the usefulness of the PEG ratio than their optimism. Finally, we report an optimised PEG trading rule which delivered annual abnormal returns of 13,7% over the study period. The trading rule appeared to single out small-capitalisation firms, with above market growth prospects, which performed well in a buoyant market.
Keywords: 650